Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]

Show Tags

13 Apr 2014, 08:03

Bunuel wrote:

Walkabout wrote:

If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =

(A) -3 (B) -1/2 (C) 0 (D) 1/2 (E) 3/2

x(2x + 1) = 0 --> x=0 OR x=-1/2; (x + 1/2)(2x - 3) = 0 --> x=-1/2 OR x=3/2.

x=-1/2 satisfies both equations.

Answer: B.

This makes complete sense, although, I ran into trouble when I tried to FOIL the second equation and ended up with x^2-x-3/4=0 and from that point forward, I was completely stumped. Why is that method wrong?

I notice that I get confused on that front quite a bit - FOIL'ing vs. just setting both parenthesis to 0?

EDIT: As I was doing other problems, I ran into DS 67, Pg 180 of OG 13. The equation there is n(n+1) = 6, if I use the same methodology outlined above, the two solutions I get are n=6 and n=5. That is obviously wrong and I should've opted to FOIL in the above case. Hence my confusion -- why is it that in some situations I need to FOIL and in some other situations, I need to just equate the left to the right side WITHOUT foiling?

Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]

Show Tags

19 May 2014, 19:43

russ9 wrote:

Bunuel wrote:

x(2x + 1) = 0 --> x=0 OR x=-1/2; (x + 1/2)(2x - 3) = 0 --> x=-1/2 OR x=3/2.

x=-1/2 satisfies both equations.

Answer: B.

This makes complete sense, although, I ran into trouble when I tried to FOIL the second equation and ended up with x^2-x-3/4=0 and from that point forward, I was completely stumped. Why is that method wrong?

I notice that I get confused on that front quite a bit - FOIL'ing vs. just setting both parenthesis to 0?

EDIT: As I was doing other problems, I ran into DS 67, Pg 180 of OG 13. The equation there is n(n+1) = 6, if I use the same methodology outlined above, the two solutions I get are n=6 and n=5. That is obviously wrong and I should've opted to FOIL in the above case. Hence my confusion -- why is it that in some situations I need to FOIL and in some other situations, I need to just equate the left to the right side WITHOUT foiling?

Hi Bunuel,

Still a little confused about the above question. I ran into countless more errors over the past few days -- cause was the same reason mentioned above. Would greatly appreciate some clarification.

x(2x + 1) = 0 --> x=0 OR x=-1/2; (x + 1/2)(2x - 3) = 0 --> x=-1/2 OR x=3/2.

x=-1/2 satisfies both equations.

Answer: B.

This makes complete sense, although, I ran into trouble when I tried to FOIL the second equation and ended up with x^2-x-3/4=0 and from that point forward, I was completely stumped. Why is that method wrong?

I notice that I get confused on that front quite a bit - FOIL'ing vs. just setting both parenthesis to 0?

EDIT: As I was doing other problems, I ran into DS 67, Pg 180 of OG 13. The equation there is n(n+1) = 6, if I use the same methodology outlined above, the two solutions I get are n=6 and n=5. That is obviously wrong and I should've opted to FOIL in the above case. Hence my confusion -- why is it that in some situations I need to FOIL and in some other situations, I need to just equate the left to the right side WITHOUT foiling?

Hi Bunuel,

Still a little confused about the above question. I ran into countless more errors over the past few days -- cause was the same reason mentioned above. Would greatly appreciate some clarification.

Thanks!

When you have that the product of several multiples is equal to zero, then you don't need to expand the product. You can directly get the answer by equating these multiples to 0.

For example: \((x - 3)(x + 2) = 0\) --> \(x - 3 = 0\) or \(x + 2 =0\) --> \(x = 3\) or \(x = -2\). Now, you could expand and get \(x^2-x-6 = 0\) and then solve with conventional method (check the links below) but the first approach is faster.

As for \(n(n+1) = 6\). Don't know how you are getting the roots for this as 5 and 6, but for this question you cannot equate the multiples (n and n+1) to zero to get the roots because the product is not zero, it's 6. To solve it, you should expand to get: \(n^2+n-6=0\) and then either solve by formula (check the links above) or by factoring to \((n+3)(n-2)=0\) and only then using the first approach: \(n + 3 = 0\) or \(n - 2 =0\) --> \(n = -3\) or \(n = 2\).

Should we apply the same logic to data sufficiency questions if we are asked to find the value of x and given each quadratic as one of the statements? Thus, statement 1 and statement 2 would each be insufficient but combining together they are sufficient (i.e. the answer is C) due to one shared solution for both quadratics/statements?

Should we apply the same logic to data sufficiency questions if we are asked to find the value of x and given each quadratic as one of the statements? Thus, statement 1 and statement 2 would each be insufficient but combining together they are sufficient (i.e. the answer is C) due to one shared solution for both quadratics/statements?

Technically, yes, C would be your answer in a similarly worded DS problem. But beware that not all quadratic equations give you 2 distinct values.

Lets say, statement 1 gave you:

\(x^2+2x+1\) = 0 , this is in fact \((x+1)^2\) ---> \((x+1)^2 = 0\)---> \(x = -1\) .

So you get ONLY 1 value and thus this statement will be sufficient on its own. Thus, in DS questions, you should be making sure that you actually are getting 2 distinct values.
_________________

Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]

Show Tags

26 Jan 2016, 16:35

I do understant the Method given by Bunuel, but I tried to look for different solution and came to the following :

Equation 1 : x(2x+1)=0 => 2x^2 +x=0 => 2x^2=-x

Equation 2: ( X+1/2)(2x+3) after FOIL => 2x^2 -2x-3/2 , and here I replaced 2x^2 with -x from the first equation and got -x-2x-3/2=o => -3x=3/2 => x=-1/2

I would like kindly ask Bunuel or other experts if this is also a correct solution?

I do understant the Method given by Bunuel, but I tried to look for different solution and came to the following :

Equation 1 : x(2x+1)=0 => 2x^2 +x=0 => 2x^2=-x

Equation 2: ( X+1/2)(2x+3) after FOIL => 2x^2 -2x-3/2 , and here I replaced 2x^2 with -x from the first equation and got -x-2x-3/2=o => -3x=3/2 => x=-1/2

I would like kindly ask Bunuel or other experts if this is also a correct solution?

Yes, this is a correct method but a bit more time consuming method. In GMAT, you must do proper time management and not just solve the questions correctly.

When you are given a*b =0 ---> 3 cases possible

1. a=0 and b \(neq\) 0

2. b=0 and a \(neq\) 0

3. a=b=0

When you are directly given x(2x + 1) = 0 --> either x=0 or 2x+1 =0 --> x=-0.5.

Similarly from the second equation, (x + 1/2)(2x - 3) = 0 ---> either x+0.5 =0 --> x=0 or 2x-3 =0 -->x=1.5.

From these 2 sets of solutions, you see that x=-0.5 is the common solution and is hence the value of x asked in the question.

Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x = [#permalink]

Show Tags

09 Jun 2016, 13:03

Walkabout wrote:

If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =

(A) -3 (B) -1/2 (C) 0 (D) 1/2 (E) 3/2

To solve we will use the zero product property. The zero product property states that if the product of two quantities is equal to 0, then at least one of the quantities has to be equal to 0. That is, if a b = 0, then either a = 0 or b = 0. Of course, both a and b can be 0 at the same time. The point is that at least one of them has to be 0.

Let’s start determining the value(s) of x in the equation x(2x + 1) = 0

If x(2x + 1) = 0, we know:

x = 0

OR

2x + 1 = 0

2x = -1

x = -1/2

Thus, x = 0 or x = -1/2

Let’s now determine the value(s) of x in the second equation (x + 1/2)(2x - 3) = 0

(x + 1/2)(2x - 3) = 0, we know:

(x + 1/2) = 0

x = -1/2

OR

(2x - 3) = 0

2x = 3

x = 3/2

Thus, x = -1/2 or x = 3/2

Because we need to determine a value for x in both equations, the answer is x = -1/2.

The answer is B.
_________________

Jeffrey Miller Scott Woodbury-Stewart Founder and CEO

gmatclubot

Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =
[#permalink]
09 Jun 2016, 13:03

Its been long time coming. I have always been passionate about poetry. It’s my way of expressing my feelings and emotions. And i feel a person can convey...

Written by Scottish historian Niall Ferguson , the book is subtitled “A Financial History of the World”. There is also a long documentary of the same name that the...

Post-MBA I became very intrigued by how senior leaders navigated their career progression. It was also at this time that I realized I learned nothing about this during my...